Perilaku Memilih Masyarakat Kelurahan Kendran pada Pilkada Kabupaten Buleleng Tahun 2017 (Studi Analisa Kekalahan PasanganxDewaxNyomanxSukrawan & I GedexDharmaxWijaya) - Raka Wibawa, I Gusti Bagus Agung; Ali Azhar, Muhammad; Bandiyah, Bandiyah (Jurnal Nawala Politika, 2019)
ABSTRACT Dewa Nyoman Sukrawan and I Gede Dharma Wijaya failed to win the Buleleng Local Election in 2017. They didn’t gain enough voters to defeat Putu Agus Suradnyana and I Nyoman Sutjidra, including in the Kendran Village which was the origin area of Dewa Nyoman Sukrawan and I Gede Dharma Wijaya. As the theoretical basis, this research uses votting behavior theory. This researchalso used the descriptive qualitative method. Data found in the field show that votting behavior in Kendran Village in Buleleng Local Election in 2017 is influenced by several voting behavior approaches. First, the sociological approach, the behavior of choosing the community is influenced by ethnic, religious, social class, and area of origin. Second, the psychological approach, the behavior of choosing the community is influenced by ties to candidates and ties to political parties. Third, the rational choice approach, where the behavior of choosing people is influenced by identification based on consideration of profit and loss. Based on these findings, it was concluded that the psychological approach and the rational choice approach were the dominant factor of kendran’s votting behavior. Keywords : Votting Behavioral, Kendran’s Society, Candidate, Buleleng Local Election 2017